Uso de fertilizante nitrogenado de liberação lenta na cultura do milho em sistema plantio direto. - Lemos, Evandro Freire (2011)
The adoption of best practices for use of fertilizers has contributed to the reduction in nutrient losses and the use of protected sources of nitrogen appears to be an interesting alternative.The aim of this study was a technical and economic evaluation of the effects of different nitrogen using slow release urea compared with traditional use of urea. The experimental design was randomized blocks with seven treatments and four replications. It was demonstrated the possibility of reducing nitrogen levels when using the slow release urea can also be applied at planting. Throughout the experiment the use of conventional urea proved more economical. It was concluded that it is necessary to popularize the techniques of protection of urea, thus making the cost of fertilizer more competitive. Treatment 3, which used 100% of the nitrogen in slow release urea at sowing showed the highest yield, and the second treatment, conventional urea applied at planting 30% and 70% coverage (merged) presented the highest net revenue per hectare, considering the costs of fertilizer.